2011
DOI: 10.1007/s11626-011-9395-6
|View full text |Cite
|
Sign up to set email alerts
|

In vitro culture of fibroblast-like cells from postmortem skin of Katahdin sheep stored at 4°C for different time intervals

Abstract: Live animals have been produced recently from animal tissues preserved for decades at frozen temperatures with or without cryoprotectants. However, the tissues in these studies were cryopreserved within few hours of animal death to obtain culturable live cells as nuclear donors. How long the tissues can be left unfrozen after animal death, without losing the viability and potential to in vitro culture with comparable morphology and proliferative rate as the fresh tissues, is not completely understood. To under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 9 publications
1
12
0
1
Order By: Relevance
“…In addition, Hjelm and colleagues generated iPSCs from fibroblasts using skin samples from a single autopsy case of a 75 year-old whole body donor [6]. Additionally, fibroblasts were recently cultured from postmortem ear tissue of sheep [7]. Culturing of postmortem tissue samples offers another avenue of study for human disease.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Hjelm and colleagues generated iPSCs from fibroblasts using skin samples from a single autopsy case of a 75 year-old whole body donor [6]. Additionally, fibroblasts were recently cultured from postmortem ear tissue of sheep [7]. Culturing of postmortem tissue samples offers another avenue of study for human disease.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the property of skin cells have differences in their behavior, as the growth curve in the days of culture under similar culture conditions. In cases of cooled tissue curve, cells reached the stationary phase on day 7 of culture as observed by Singh et al (2011) and Singh & Xiaoling (2014). Nevertheless, Mahesh et al (2012) observed the same culture conditions at the beginning of the stationary phase on day 4 of the curve.…”
Section: Discussionmentioning
confidence: 56%
“…Ear skin was cleaned, first with tape water and subsequently with 70% alcohol swabs, wrapped in clean sterile paper towels, and stored in the laboratory in an incubator set at 35°C. Small slices were excised aseptically from the ear skin, chopped into small explants (2-3 mm Primary outgrowing cells were trypsinized on day 10-12 of culture to recover outgrowing cells as described (Singh et al 2011). Briefly, the cells in dishes were washed twice with 1.0 mL of the balanced salt solution without calcium and magnesium (Gibco, Carlsbad, CA) and incubated with 1.0 mL of 0.125% trypsin for 5-7 min at 37°C followed by neutralization with 5 vol.…”
Section: Methodsmentioning
confidence: 99%